TINGKAT KOMPETISI PERUSAHAAN SEMEN DI INDONESIA BERBASIS STRUKTUR PASAR - Nadhira Amri; Sofyan Syahnur; Vivi Silvia (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2022)
Abstract                                                                                                                 The purpose of this study is to analyze the competition that occurs between cement companies in Indonesia and to determine the market structure of the cement industry in Indonesia. The data used is secondary data, secondary data obtained from the Indonesian Cement Association, Workshop Data, and Industrial Research Data. The analytical tools used are CRN (Concentration Ratio), HHI (Herfindahl-Hirschman Index) and Game Theory. Descriptive analysis is used to describe the level of competition in terms of product development strategy, production strategy and distribution strategy. The use of game theory in price competition is said to be balanced because both companies offer products at affordable prices. Based on the method of concentration ratio of the four highest companies (CR4), the market structure of the cement industry in Indonesia in 2020 is classified as a concentrated oligopoly or a full oligopoly. Based on the Herfindahl-Hirschman Index (HHI) method, the cement industry in Indonesia in 2020 is classified as concentrated. Keywords : Level of Competition, Market Structure, Cement Company, Game Theory